Attitudes and emotions as predictors of support for wolf management. (December 2021) - Vaske, Jerry J.; Miller, Craig A.; Pallazza, Samantha; Williams, Brent
Abstract: Predictive models analyzing relationships among emotions, attitudes, behavioral intentions have inconsistently examined the implied logical flow of the concepts. This article examined two research questions. When general attitude and general emotional dispositions are predictors of support for specific wolf management actions: (a) should a direct effects, a partial mediation model, or a full mediation model be analyzed; and (b) should attitudes or emotions be the mediator? Data were obtained from a mail survey of Illinois residents ( n  = 2, 634, response rate = 48%). Five structural equation models were examined. The partial mediation model with attitude as the mediator had the best fit, followed by the partial mediation model with emotion as the mediator. Both positive and negative emotions were more strongly related to support for wolf management than attitude. This may have occurred because a general attitude, as opposed to a specific attitude, was examined. This article examined behavioral intentions; future research should measure actual behaviors or reported behaviors. Highlights: Research has empirically examined different path models for the relationships among emotions, attitudes, and behaviors: Emotion → Attitude → Behavior Attitude → Emotion → Behavior Using structural equation analyses, this article compared five nested path models for both formulations of the relationships. The partial mediation model with attitude as the mediator had the best fit for the data. Both positive and negative emotional dispositions had a larger relationship with support for wolf management than attitude.